Independent predictors and clinical predictive score of postanesthetic reintubation after general anesthesia: A time-matched, case control study - Chidchanok Choovongkomol; Thidarat Ariyanuchitkul; Kongtush Choovongkomol; Vipanee Tongjapo (Journal of Anaesthesiology Clinical Pharmacology)
Background and Aims: Postanesthetic reintubation is associated with increased morbidities and mortality; however, it can be reduced with defined predictors and using a score as a tool. This study aimed to identify independent predictors and develop a reliable predictive score. Material and Methods: A retrospective, time-matched, case control study was conducted on patients who underwent general anesthesia between October 2017 and September 2021. Using stepwise multivariable logistic regression analysis, predictors were determined and the predictive score was developed and validated. Results: Among 230 patients, 46 were in the reintubated group. Significant independent predictors included age >65 years (odds ratio [OR] 2.96 [95% confidence interval CI 1.23, 7.10]), the American Society of Anesthesiologists physical status III–IV (OR 6.60 [95%CI 2.50 17.41]), body mass index (BMI) ≥30 kg/m2 (OR 4.91 [95% CI 1.55, 15.51]), and head and neck surgery (OR 4.35 [95% CI 1.46, 12.87]). The predictive model was then developed with an area under the receiver operating characteristic curve (AUC) of 0.84 (95% CI 0.78, 0.90). This score ranged from 0 to 29 and was classified into three subcategories for clinical practicability, in which the positive predictive values were 6.01 (95% CI 2.63, 11.50) for low risk, 18.64 (95% CI 9.69, 30.91) for moderate risk, and 71.05 (95% CI 54.09, 84.58) for high risk. Conclusion: The independent predictors for postanesthetic reintubation according to this simplified risk-based scoring system designed to aid anesthesiologists before extubation were found to be advanced age, higher American Society of Anesthesiologists physical status, obesity, and head and neck surgery.